2021
DOI: 10.1016/j.apsb.2021.05.032
|View full text |Cite
|
Sign up to set email alerts
|

MCDB: A comprehensive curated mitotic catastrophe database for retrieval, protein sequence alignment, and target prediction

Abstract: Mitotic catastrophe (MC) is a form of programmed cell death induced by mitotic process disorders, which is very important in tumor prevention, development, and drug resistance. Because rapidly increased data for MC is vigorously promoting the tumor-related biomedical and clinical study, it is urgent for us to develop a professional and comprehensive database to curate MC-related data. Mitotic Catastrophe Database (MCDB) consists of 1214 genes/proteins and 5014 compounds collected and organized from more than 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 62 publications
0
29
0
Order By: Relevance
“…In the first turn, small-molecule compound databases including SPECS, ACDB, and MCDB with more than 200,000 compounds were filtered by the Lipinski's rule of five. 19 It is well known that the molecule with the following features would be more likely to result in a real small-molecule drug: (1) a molecular mass less than 500 Da; (2) no more than 10 hydrogen bond acceptors; (3) no more than five hydrogen bond donors; and (4) log P (octanol–water partition coefficient) no greater than 5. 20 In addition, all of these compounds are commercially available or synthesized in laboratory, and could be picked out for further biological evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…In the first turn, small-molecule compound databases including SPECS, ACDB, and MCDB with more than 200,000 compounds were filtered by the Lipinski's rule of five. 19 It is well known that the molecule with the following features would be more likely to result in a real small-molecule drug: (1) a molecular mass less than 500 Da; (2) no more than 10 hydrogen bond acceptors; (3) no more than five hydrogen bond donors; and (4) log P (octanol–water partition coefficient) no greater than 5. 20 In addition, all of these compounds are commercially available or synthesized in laboratory, and could be picked out for further biological evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we first collected experimentally identified proteins from PubMed by using multiple keywords, such as 'apoptosis', 'apoptotic', 'anoikis', 'cytotoxic granulemediated cell death', 'oxeiptosis', 'necroptosis', 'necrosis', 'necrotic', 'pyroptosis', 'oncosis', 'oncotic', 'pyronecrosis', 'alkaliptosis', 'autophagic', 'autophagy', 'autosis', 'lysosomal cell death', 'autolysis', 'cornification', 'entosis', 'entotic', 'ferroptosis', 'hypersensitive response', 'mitoptosis', 'paraptosis', 'excitotoxicity', 'NETosis', 'netotic', 'parthanatos', 'phenoptosis', 'heterokaryon incompatibility', 'mitotic catastrophe', 'Wallerian degeneration', 'oxiapoptophagy', 'immunogenic cell death', 'phagoptosis', 'sarmoptosis' and 'PANoptosis'. In addition, we also integrated downloadable data resources from 11 PCD databases, including DeathBase [21], yApoptosis [22], CDP [23], Autophagy Database [24], HADb [25], ARN [26], HAMdb [27], ATdb [28], FerrDb [29], MCDB [30] and ncRDeathDB [32] (Figure 1A, Supplementary Methods). In order to ensure the quality of data, we carefully read the abstracts and the full text of papers.…”
Section: Data Collection and Curationmentioning
confidence: 99%
“…Therefore, GPX4 protein is tagged with '−' as a negative regulator of ferroptosis (Figure 1A). In addition, we also integrated downloadable data resources from 11 PCD databases, including DeathBase [21], yApoptosis [22], CDP [23], Autophagy Database [24], HADb [25], ARN [26], HAMdb [27], ATdb [28], FerrDb [29], MCDB [30] and ncRDeathDB [32] (Figure 1A, Supplementary Methods). In order to ensure the quality of data, we carefully read the abstracts and the full text of papers.…”
Section: Data Collection and Curationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, future state prediction for a multi-omics time series has been widely studied by computational biologists. For genomic studies, we usually use a gene expression time series to develop gene regulatory networks ( Davidson and Levin 2005 ; Zhang et al, 2018 ; Xiao et al, 2020 ; Zhang et al, 2020 ; Xiao et al, 2021 ; Zhang et al, 2021a ). However, since the gene regulatory network is a complex high-dimensional nonlinear system ( Zhang et al, 2012a ), it often produces chaotic phenomena ( Levnajić and Tadić 2010 ), which not only play an important role in maintaining stable gene expression patterns ( Sevim and Rikvold 2008 ) but also are closely related to the occurrence of diseases ( Suzuki et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%